2020
DOI: 10.18240/ijo.2020.12.21
|View full text |Cite
|
Sign up to set email alerts
|

Proportion and characteristic of emmetropia in schoolchildren aged 6-11y: the Shenzhen elementary school eye study

Abstract: AIM: To investigate the proportion and characteristic of emmetropia in schoolchildren aged 6-11, especially estimate the normal value of ocular biometric parameters of emmetropia. METHODS: A population-based cross-sectional study was conducted on children aged 6-11y in Shenzhen. Totally, 2386 schoolchildren from two primary schools were involved. The axial length (AL) and the corneal radius of curvature (CRC) were measured by partial coherence laser interferometry. Noncycloplegic refraction and refractive asti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…No significant difference between the myopia risk groups for AXL (F 1,95 = 0.05, p = 0.83; HR: 22.80 ± 0.64 mm; LR: 22.77 ± 0.67 mm), PVD (F 1,91 = 1.44, p = 0.23; HR: 15.89 ± 0.95 mm; LR: 15.67 ± 0.83 mm) and AXL/CR (F 1,950 = 1.80, p = 0.84; HR: 2.96 ± 0.01; LR: 2.94 ± 0.01) was observed when all subjects were included. As expected, male eyes were significantly longer than female eyes (t = 3.12, p < 0.01; females: 22.60 ± 0.66 mm; males: 23.00 ± 0.59 mm), 49,64,[74][75][76][77][78] and when subjects were divided by sex, AXL was longer in the HR compared with the LR group (F 2,94 = 4.89, p = 0.01; estimated corrected means HR: 22.81 ± 0.09 mm; LR: 22.77 ± 0.09 mm).…”
Section: R Esultssupporting
confidence: 77%
See 3 more Smart Citations
“…No significant difference between the myopia risk groups for AXL (F 1,95 = 0.05, p = 0.83; HR: 22.80 ± 0.64 mm; LR: 22.77 ± 0.67 mm), PVD (F 1,91 = 1.44, p = 0.23; HR: 15.89 ± 0.95 mm; LR: 15.67 ± 0.83 mm) and AXL/CR (F 1,950 = 1.80, p = 0.84; HR: 2.96 ± 0.01; LR: 2.94 ± 0.01) was observed when all subjects were included. As expected, male eyes were significantly longer than female eyes (t = 3.12, p < 0.01; females: 22.60 ± 0.66 mm; males: 23.00 ± 0.59 mm), 49,64,[74][75][76][77][78] and when subjects were divided by sex, AXL was longer in the HR compared with the LR group (F 2,94 = 4.89, p = 0.01; estimated corrected means HR: 22.81 ± 0.09 mm; LR: 22.77 ± 0.09 mm).…”
Section: R Esultssupporting
confidence: 77%
“…38,85,87 Nevertheless, LT decreased significantly with age in children between 6 and 9 years, as previously reported. 38,49,88 The differences found with prior studies may also be driven by age.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Table 1 describes the change characteristics of ocular biological parameters in different sexes. Previous researches showed that the rate of myopic shift in refraction increases as myopia develops, but it usually increased before children aged ≤ 17 years, and the major determinant of the rate of progression was age, with little dependence on the level of myopia [ 16 19 ]. The present study found that the myopic participants showed a significantly faster change in △AL towards myopia than emmetropic participants at baseline.…”
Section: Discussionmentioning
confidence: 99%